Sociology of Sexual Education in Algerian Society - a field study - Otmani, Hebib; Krissat, Zohra (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2022)
Sociology of Gender is a subject that left social institutions in silence, and it led to society expressing it with defamatory acts, images and symbols, and with the multiple social, political, economic and technological transformations society had known, the propagation of sexual consummation ideology has risen above some religious values. It has driven to this theoretical and practical study to help propose a scientific program that will be teached in schools by teachers and professors that are competent in the field of sexual education and thus build a generation with healthy and correct personality and protect the natural cultural environment. Because our children have multiple interrogations from their childhood to their maturity about sexual acts and STD, we need to build a pedagogical program who will provide children with the needed physiologic knowledge and even more, with the good values and principles. That’s why it is necessary to comprehend how is sexual education characterized for high school students, but how to do so? And how to use this comprehension in the construction of this educational program?